Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper highlights the growth process in Belarus, seeking to identify its main sources and assess its sustainability. It complements the IMF staff report, which placed considerable emphasis on macroeconomic policies. It provides an overview of additional important factors underlying Belarus's recent economic performance. It presents some further insights on the likely future path of main macroeconomic variables. The analysis suggests that, although several aspects of Belarus's macroeconomic performance have been unusual, it is clear that domestic policies and favorable exogenous factors have combined to boost growth in recent years.